A stereophotogrammetric technique for forensic measurement of surveillance images - M. Ariff, M. Farid; Setan, Halim; Majid, Zulkepli; Albert, K. Chong (2008)
The paper provides a discussion about new approach to detect criminal suspect through camera images with the integration of surveillance camera system and close-range photogrammetry technique. The setting up of the surveillance camera system is based on the stereo photogrammetric mode. For high accuracy photogrammetric measurement, the space which was covered in the surveillance cameras field of view (FOV) was calibrated using special-built a portable high precision control frame. Via close-range photogrammetry technique, the physical morphology (example: anthropometry of facial features) of the suspect can be measured accurately in 3D environment (stereo measurement).